GUERRERO GUERRERO, A. L. (2024). Gatopardismo en la ONU para las políticas de desarrollo. CIALC-UNAM/Ediciones Eón. - Andrada-Zurita, Carolina (Daimon Revista Internacional de Filosofia, 2026)
Reseña de GUERRERO GUERRERO, A. L. (2024). Gatopardismo en la ONU para las políticas de desarrollo. CIALC-UNAM/Ediciones Eón.